Basket of agricultural technologies and innovations in West and Central Africa: Priority options from CORAF - Ganyo, Komla Kyky; Kpadonou, G Esaïe; Lamien, Niéyidouba; Sobgui, Caroline Makamto; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The West and Central African Council for Agriculture and Research Development (CORAF) is an umbrella organization of national agricultural research systems (NARS) in 23 countries in West and Central Africa, consisting of public agricultural research institutes, universities and other tertiary institutions, farmer groups, civil society organizations, the private sector and any other entity engaged in the provision of agricultural research services. Together with its partners in West and Central Africa, CORAF has generated over 320 agricultural technologies and innovations for improving agricultural productivity and livelihoods. The technologies and innovations developed ranged from crop varieties, livestock breeds and sowing technologies to post-harvest technologies and innovations along several agricultural value chains such as roots and tubers, dry cereals, rice, plantain, milk and meat and fish. This portfolio of technologies and innovations serves a “basket” from which options can be selected, tested and up scaled to address specific climatic and non-climatic risks across West and Central Africa agroecological contexts. Seizing the opportunity of AICCRA to assess climate-smartness and gender-sensitivity of the technologies and innovations is the next step to facilitate effective targeting and scaling.